2022
DOI: 10.1111/jonm.13806
|View full text |Cite
|
Sign up to set email alerts
|

Nurse leaders' work‐related well‐being—Relationships to a superior's transformational leadership style and structural empowerment

Abstract: Aims To describe how nurse leaders' work‐related well‐being is related to a superior's transformational leadership style and structural empowerment. Background The demanding role of nurse leader means that these professionals experience emotional exhaustion and challenges with work–life balance. They can also be influenced by the leadership style of their own superiors. Methods A cross‐sectional questionnaire using two internationally validated scales, namely, the Transformational Leadership Scale and Conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…This indicated that organizational effort could be invested in improving nurses' access to empowerment structures to mitigate medical errors. A supportive and empowering organizational structure can be achieved through fostering open communication, professional development opportunities, and shared decision-making [ 31 ]. Consequently, healthcare professionals working in such an environment are better equipped to provide safe and effective patient care [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that organizational effort could be invested in improving nurses' access to empowerment structures to mitigate medical errors. A supportive and empowering organizational structure can be achieved through fostering open communication, professional development opportunities, and shared decision-making [ 31 ]. Consequently, healthcare professionals working in such an environment are better equipped to provide safe and effective patient care [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…To allocate more time for management and leadership, for example, staff relations and support, organisations should develop effective practices. Moreover, hiring assistants to manage staffing and the recruitment of personnel could be enhanced ( Mericle et al., 2023 ; Niinihuhta et al., 2022b ).…”
Section: Discussionmentioning
confidence: 99%